2017
DOI: 10.1038/tp.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Restoring effects of oxytocin on the attentional preference for faces in autism

Abstract: Reduced attentional preference for faces and symptoms of social anxiety are common in autism spectrum disorders (ASDs). The neuropeptide oxytocin triggers anxiolytic functions and enhances eye gaze, facial emotion recognition and neural correlates of face processing in ASD. Here we investigated whether a single dose of oxytocin increases attention to faces in ASD. As a secondary question, we explored the influence of social anxiety on these effects. We tested for oxytocin's effects on attention to neutral face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 68 publications
1
45
1
1
Order By: Relevance
“…Taken together, these studies highlight that looking behavior in autism versus typical development may be at least partially explained by the presence of anxiety [Corden et al, ; Kanat et al, ]. Considering the literature on neurotypical samples, high levels of social anxiety have been found to be associated with decreased looking at emotional faces [Garner, Mogg, & Bradley, ].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Taken together, these studies highlight that looking behavior in autism versus typical development may be at least partially explained by the presence of anxiety [Corden et al, ; Kanat et al, ]. Considering the literature on neurotypical samples, high levels of social anxiety have been found to be associated with decreased looking at emotional faces [Garner, Mogg, & Bradley, ].…”
Section: Resultsmentioning
confidence: 97%
“…Lastly, a study examined the effect of delivering intranasal oxytocin ( versus placebo) on looking behavior among adults with and without autism [Kanat et al, ]. Using a dot‐probe paradigm with face and house images, results showed that those with autism who received the placebo looked less at faces than neurotypical adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, initial allocation of attention to faces is much weaker in patients with ASD, with high level of social anxiety. Reduced attentional preference for faces and symptoms of social anxiety are common in ASD . It could reflect arousal‐related attentional avoidance rather than reduced stimulus salience .…”
mentioning
confidence: 99%
“…Reduced attentional preference for faces and symptoms of social anxiety are common in ASD . It could reflect arousal‐related attentional avoidance rather than reduced stimulus salience . The amygdaloid network might be overactive in individuals with ASD, leading to aversive experience when looking at faces early in the development.…”
mentioning
confidence: 99%